An Engineered IFNγ-Antibody Fusion Protein with Improved Tumor-Homing Properties - Cesare Di Nitto; Ettore Gilardoni; Jacqueline Mock; Lisa Nadal; Tobias Weiss; Michael Weller; Frauke Seehusen; Chiara Libbra; Emanuele Puca; Dario Neri; Roberto De Luca (MDPI AG, 2023)
Interferon-gamma (IFNγ) is one of the central cytokines produced by the innate and adaptive immune systems. IFNγ directly favors tumor growth control by enhancing the immunogenicity of tumor cells, induces IP-10 secretion facilitating (CXCR3+) immune cell infiltration, and can prime macrophages to an M1-like phenotype inducing proinflammatory cytokine release. We had previously reported that the targeted delivery of IFNγ to neoplastic lesions may be limited by the trapping of IFNγ-based products by cognate receptors found in different organs. Here we describe a novel fusion protein consisting of the L19 antibody, specific to the alternatively spliced extra-domain B of fibronectin (EDB), fused to a variant of IFNγ with reduced affinity to its cognate receptor. The product (named L19-IFNγ KRG) selectively localized to tumors in mice, showed favorable pharmacokinetic profiles in monkeys and regained biological activity upon antigen binding. The fusion protein was investigated in two murine models of cancer, both as monotherapy and in combination with therapeutic modalities which are frequently used for cancer therapy. L19-IFNγ KRG induced tumor growth retardation and increased the intratumoral concentration of T cells and NK cells in combination with anti-PD-1.